Commentary: COVID in care homes—challenges and dilemmas in healthcare delivery. (13th May 2020) - Gordon, Adam L; Goodman, Claire; Achterberg, Wilco; Barker, Robert O; Burns, Eileen; Hanratty, Barbara; Martin, Finbarr C; Meyer, Julienne; O'Neill, Desmond; Schols, Jos; Spilsbury, Karen
Abstract: The COVID-19 pandemic has disproportionately affected care home residents internationally, with 19–72% of COVID-19 deaths occurring in care homes. COVID-19 presents atypically in care home residents and up to 56% of residents may test positive whilst pre-symptomatic. In this article, we provide a commentary on challenges and dilemmas identified in the response to COVID-19 for care homes and their residents. We highlight the low sensitivity of polymerase chain reaction testing and the difficulties this poses for blanket screening and isolation of residents. We discuss quarantine of residents and the potential harms associated with this. Personal protective equipment supply for care homes during the pandemic has been suboptimal and we suggest that better integration of procurement and supply is required. Advance care planning has been challenged by the pandemic and there is a need to for healthcare staff to provide support to care homes with this. Finally, we discuss measures to implement augmented care in care homes, including treatment with oxygen and subcutaneous fluids, and the frameworks which will be required if these are to be sustainable. All of these challenges must be met by healthcare, social care and government agencies if care home residents and staff are to be physically and psychologically supported during this time of crisis for care homes.